Formulation and evaluation of Anti-aging Serum Containing a Combination of Mugwort (Artemisia capillaris) Extract and Vitamin C as an Antioxidant - Utami, Fit Indri Intan; Qodriah, Rahmatul; Budiati, Anarisa; Mumpuni, Esti (Journal of Natural Product for Degenerative Diseases, 2023)
Mugwort (genus Artemisia) is a skincare ingredient originating from a South Korean beauty trend having antioxidant properties and is currently popular globally. The aim of this research is to formulate and determine the antioxidant activity of anti-aging serum containing Mugwort (Artemisia capillaris) and Vitamin C extract as antioxidants. All formulas were adjusted to a pH range of 5.0 – 5.2. Each formula was characterized based on antioxidant activity using the DPPH method. Serum with mugwort extract (F1) and serum with a combination of mugwort extract and vitamin C (F3) show strong antioxidant activity with an IC50 of 99.70 and 82.92 ppm, respectively. Anti-aging serum containing mugwort (Artemisia capillaris) extract and vitamin C provides strong antioxidant activity with an IC50 of 82.92 ppm (F3).